Impact of cyclic loading on longitudinally-reinforced UHPC flexural members with different fiber volumes and reinforcing ratios. (15th August 2021) - Shao, Yi; Billington, Sarah L.
Highlights: Cyclic loading reduces reinforced UHPC flexural strength and deformation capacity. Cyclic loading reduces UHPC fiber-bridging capacity. Fiber distribution impacts structural performance under different loading directions. Reducing fiber volume increases UHPC structural ductility under monotonic and cyclic loading. Abstract: Ultra-high performance concrete (UHPC) is a promising material for many structural applications given its high compressive strength, its tensile ductility, and its potential durability through low permeability. Most research on steel reinforced UHPC (R/UHPC) flexural components has focused on monotonic performance and less is known about R/UHPC cyclic performance. Additionally, the steel fibers, which typically comprise 2% of the volume of a UHPC mix and account for 30% of the material cost, could potentially be reduced to improve both cost efficiency and performance of R/UHPC components. This study explores the impact of high-amplitude cyclic loading on R/UHPC beams with different fiber volumes (1% and 2%) and reinforcing ratios (0.96% and 2.10%). A total of eight simply-supported beam experiments are compared in this study. Results show that for both monotonic and cyclically-loaded specimens, a higher reinforcing ratio and a lower fiber volume introduce more localized cracks, delay steel fracture, and increase R/UHPC deformation capacity. Compared to monotonically-loaded beams, cyclic loading reduces UHPC fiber-bridging capacity, resulting in lower component yield and peak strength as well as more localized cracks. The deformation capacity of cyclically-loaded beams is also lower than that of monotonically-loaded beams due to low cycle fatigue of the reinforcing steel. Differing fiber distributions due to material flow during casting were also found to impact the structural performance under different loading directions. A flexural failure path prediction method for R/UHPC is validated by both the monotonic and cyclic results.